1999
DOI: 10.1086/307110
|View full text |Cite
|
Sign up to set email alerts
|

The Diffuse Gamma‐Ray Background from Supernovae

Abstract: The diffuse extragalactic γ-ray background in the MeV region is believed to be due to photons from radioactivity produced in supernovae throughout the history of galaxies in the universe. In particular, γ-ray line emission from the decay chain 56 Ni → 56 Co → 56 Fe provides the dominant photon source (Clayton & Silk 1969). Although iron synthesis occurs in all types of supernovae, the contribution to the background is dominated by Type Ia events due to their higher photon escape probabilities. Estimates of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 62 publications
3
82
0
Order By: Relevance
“…Our results are comparable to those of previous studies. Although early studies showed large contributions from SNe Ia (Clayton & Silk 1969;Clayton & Ward 1975;The et al 1993;Zdziarski 1996;Watanabe et al 1999;Ruiz-Lapuente et al 2001), later studies report contributions to be ∼10 (Strigari et al 2005) and 10 ) less than the measured intensity. If the dominant fraction of the CGB could be subtracted by future detectors, the SN Ia contribution could be detected.…”
Section: Contribution To the Cosmic Gamma-ray Backgroundmentioning
confidence: 82%
“…Our results are comparable to those of previous studies. Although early studies showed large contributions from SNe Ia (Clayton & Silk 1969;Clayton & Ward 1975;The et al 1993;Zdziarski 1996;Watanabe et al 1999;Ruiz-Lapuente et al 2001), later studies report contributions to be ∼10 (Strigari et al 2005) and 10 ) less than the measured intensity. If the dominant fraction of the CGB could be subtracted by future detectors, the SN Ia contribution could be detected.…”
Section: Contribution To the Cosmic Gamma-ray Backgroundmentioning
confidence: 82%
“…1). As discussed by several authors [5,6,7], type Ia supernovae could make a significant contribution in this energy range, which we shall evaluate in Section 2.…”
Section: Introductionmentioning
confidence: 93%
“…In the GeV regime the MRF seems to originate from unresolved blazars and galaxies. Gamma rays emitted by novae, supernovae, and γ-ray bursts contribute the bulk of the observed background in the window around 1 MeV (e.g., Watanabe et al 1999;Weidenspointner 1999;Ruiz-Lapuente et al 2000). In principle, the evolution of the MRF should be predictable with structure formation models (e.g., Sommerville & Primack 1999), so that the observed MRF could be used to infer either the role of AGNs, low surface brightness objects, decays of relic particles, or to single out cosmological parameters.…”
Section: Introductionmentioning
confidence: 99%